Studies on relative fitness and off-season activity of castor capsule borer, Conogethes punctiferalis Guenee (Lepidoptera : Crambidae): STUDIES ON RELATIVE FITNESS AND OFF-SEASON ACTIVITY OF CASTOR CAPSULE BORER - P DURAIMURUGAN; M LAKSHMINARAYANA (Journal of Oilseeds Research, 2016)
Castor capsule borer, Conogethes punctiferalis Guenee is a keypest of economic importance in the rainfed castor belts of Telangana, Andhra Pradesh and Karnataka. The polyphagous pest was found to infest 36 crop plants in India. In the recent years, occurrence of host races or cryptic species have been reported in different host-associated populations of C. punctiferalis. In the present study, oviposition responses and relative fitness of C. punctiferalis on five economically important hosts viz., castor, ginger, turmeric, maize and guava was studied under laboratory conditions. Among five hosts, C. punctiferalis preferred castor and maize for oviposition, while there was no oviposition was recorded on ginger, turmeric and guava. The fecundity, per cent hatching, pupation and adult emergence was 23.6 and 18.6 eggs, 64.4 and 60.2 per cent, 87.7 and 87.3 per cent and 94.9 and 93.0 per cent on castor and maize, respectively. The average larval and pupal periods were 17.15 and 8.27 days on castor, while it was 18.1 and 8.76 days on maize. Field survey was conducted to study off-season activity and carry-over of castor capsule borer, C. punctiferalis during March to July, 2014 and 2015. Among 12 alternate hosts surveyed, off-season multiplication of C. punctiferalis was recorded on perennial castor, guava fruits and mango inflorescence in both the years. Laboratory rearing of the larvae and pupae of C. punctiferalis collected on the alternate hosts revealed that there was no diapause in any stage ofits life cycle during the off-season. The present results provide informative data on relative fitness and off-season activity of C. punctiferalis on alternate hosts will be useful in developing strategies for the management of this pest.